Security and Privacy Challenges in Cloud-Based Telemedicine for Medical Tourism: A Systematic Literature Review - Amu, Christopher Onyebuchi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
Telemedicine has witnessed rapid growth, especially in the context of medical tourism. This systematic literature review explores the security and privacy challenges associated with the integration of cloud-based telemedicine in the realm of medical tourism. The study employs the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method to ensure a comprehensive and transparent review process. This review extensively scrutinizes scholarly articles, reports, and case studies published in reputable journals and conference proceedings from 2010 to 2024. With an in-depth assessment of over 50 papers, research highlights the advancements in telemedicine for medical tourism while shedding light on the critical issues related to data security and patient privacy. The identified challenges encompass regulatory compliance, information vulnerability, and ethical considerations. In-depth analysis of various scholarly works provides insights into the existing gaps and areas requiring attention. To address these challenges, this thesis proposes IT-based solutions aimed at enhancing the security posture and privacy measures in cloud-based telemedicine systems catering to medical tourism. These solutions encompass robust encryption protocols, secure data storage practices, and compliance frameworks tailored to the unique nature of medical tourism. In summary, this systematic literature review not only unveils the complexities surrounding the intersection of cloud-based telemedicine and medical tourism but also offers IT-based solutions to fortify the security and privacy aspects, ensuring a safer and more reliable healthcare delivery system.

ÖZ: Teletıp, özellikle medikal turizm bağlamında hızlı bir büyümeye tanık oldu. Bu sistematik literatür taraması, bulut tabanlı teletıpın medikal turizm alanına entegrasyonuyla ilişkili güvenlik ve gizlilik zorluklarını araştırıyor. Çalışmada kapsamlı ve şeffaf bir inceleme süreci sağlamak için PRISMA (Sistematik İncelemeler ve Meta-Analizler için Tercih Edilen Raporlama Öğeleri) yöntemi kullanılmaktadır. Bu inceleme, 2010'dan 2024'e kadar saygın dergilerde ve konferans tutanaklarında yayınlanan bilimsel makaleleri, raporları ve vaka çalışmalarını kapsamlı bir şekilde incelemektedir. 50'den fazla makalenin derinlemesine değerlendirmesiyle araştırma, sağlık turizmi için teletıptaki ilerlemeleri vurgularken, kritik öneme sahip konulara ışık tutmaktadır. Veri güvenliği ve hasta mahremiyetiyle ilgili konular. Tanımlanan zorluklar mevzuat uyumluluğunu, bilgi zafiyetini ve etik hususları kapsamaktadır. Çeşitli bilimsel çalışmaların derinlemesine analizi, mevcut boşluklara ve dikkat edilmesi gereken alanlara ışık tutar. Bu zorlukların üstesinden gelmek için bu tez, medikal turizme hizmet veren bulut tabanlı teletıp sistemlerinde güvenlik durumunu ve gizlilik önlemlerini geliştirmeyi amaçlayan BT tabanlı çözümler önermektedir. Bu çözümler, sağlam şifreleme protokollerini, güvenli veri depolama uygulamalarını ve medikal turizmin benzersiz doğasına uygun hale getirilmiş uyumluluk çerçevelerini kapsar. Özetle, bu sistematik literatür taraması yalnızca bulut tabanlı teletıp ve medikal turizmin kesişimini çevreleyen karmaşıklıkları ortaya çıkarmakla kalmıyor, aynı zamanda güvenlik ve mahremiyet yönlerini güçlendirerek daha güvenli ve daha güvenilir bir sağlık hizmeti sunum sistemi sağlayan BT tabanlı çözümler de sunuyor.
Master of Technology in Information Technology. Institute of Graduate Studies and Research. Thesis (M.Tech.) - Eastern Mediterranean University, School of Computing and Technology, 2024. Supervisor: Asst. Prof. Dr. Akile Oday Gilol.
Keywords: School of Computing and Technology; Cloud Computing--Security--Telemedicine; Cloud-based Telemedicine, Medical Tourism, Security and Privacy challenges